2022
DOI: 10.3390/app12136618
|View full text |Cite
|
Sign up to set email alerts
|

An Accurate UAV Ground Landing Station System Based on BLE-RSSI and Maximum Likelihood Target Position Estimation

Abstract: Earth observation with unmanned aerial vehicles (UAVs) offers an extraordinary opportunity to bridge the gap between field observations and traditional air and space-borne remote sensing. In this regard, ground landing stations (GLS) systems play a central role to increase the time and area coverage of UAV missions. Bluetooth low energy (BLE) technology and the received signal strength indicator (RSSI) techniques have been proposed for target location during UAV landing. However, these RSSI-based techniques pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In [47], wireless positioning technology was applied to UAV (unmanned aerial vehicle) landing, and a prototype UAV ground landing station based on BLE-RSSI was proposed in combination with maximum likelihood estimation and the trilingual measurement algorithm. The results showed that BLU-RSSI could determine the location target more accurately when the UAV was within 5 m of the ground landing station platform.…”
Section: Optimization Based On Database Matching Methodsmentioning
confidence: 99%
“…In [47], wireless positioning technology was applied to UAV (unmanned aerial vehicle) landing, and a prototype UAV ground landing station based on BLE-RSSI was proposed in combination with maximum likelihood estimation and the trilingual measurement algorithm. The results showed that BLU-RSSI could determine the location target more accurately when the UAV was within 5 m of the ground landing station platform.…”
Section: Optimization Based On Database Matching Methodsmentioning
confidence: 99%
“…Representing an enhanced version of Bluetooth, BLE is designed for applications that require short range demands with low power, having the same bit rate, frequency range (i.e., from 2.4 GHz to 2.48 GHz), and range of traditional Bluetooth [241]. In combination with the Received Signal Strength Indicator (RSSI) technique, the BLE-RSSI combined method presented a lack of precision in UAV positioning, which was overcome in [242]. With regard to UAV navigation in GNSS-denied environments, an indoor positioning system for UAVs is set up through BLE beacons by analyzing the RSSI, where the final position estimation is acquired by trilateration [243].…”
Section: (C) Blementioning
confidence: 99%
“…The most significant data rate that BLE can accomplish is 1Mbps, which may not always be sufficient for devices like wireless headphones that demand continuous data streaming (Avilés-Viñas et al, 2022;Barsocchi, Girolami, & La Rosa, 2021;Belwafi, Alkadi, Alameri, Al Hamadi, & Shoufan, 2022;Cantizani-Estepa et al, 2022). On the other hand, another internet of thing application requires periodic small data transmissions.…”
Section: Bluetooth Low Energy (Ble)mentioning
confidence: 99%